2020
DOI: 10.1016/j.jfoodeng.2019.109822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the frequency of weak oscillating magnetic fields on supercooling and freezing kinetics of pure water and 0.9% NaCl solutions

Abstract: Several studies in the literature suggest that the frequency of weak oscillating magnetic fields (OMFs) significantly affects supercooling and freezing kinetics, although the effects described by different authors are apparently contradictory. To shed light on this matter, we froze pure water samples and 0.9% NaCl solutions in a 0.8-mT magnetic field at different frequencies (20, 50, 200, and 2000 Hz). Moreover, experiments with no OMF application were also performed to act as controls. Our results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The optimization and employing proper strength of the magnetic field is controversial. Otero, Rodríguez [145] indicated that a 0.8-mT OMF did not affect the supercooling degree and freezing kinetics of pure water and 0.9% NaCl solution. Moreover, under the weak (107-359 mT) SMF, no significant effects were reported by Otero, Rodríguez [146].…”
Section: Magnetically Disturbed Freezingmentioning
confidence: 95%
See 1 more Smart Citation
“…The optimization and employing proper strength of the magnetic field is controversial. Otero, Rodríguez [145] indicated that a 0.8-mT OMF did not affect the supercooling degree and freezing kinetics of pure water and 0.9% NaCl solution. Moreover, under the weak (107-359 mT) SMF, no significant effects were reported by Otero, Rodríguez [146].…”
Section: Magnetically Disturbed Freezingmentioning
confidence: 95%
“…OMF is also commercially known as CAS (Cells Alive System) freezer. OMF is produced by permanent magnets, while SMF is generated by magnetic coils [142].…”
Section: Magnetically Disturbed Freezingmentioning
confidence: 99%
“…The ice crystal size is strongly dependent on the degree of supercooling (i.e., the difference between the nucleation and initial freezing temperatures) [ 44 ]. Generally, low supercooling degrees cause large ice crystals to form in intercellular spaces and high supercooling degrees result in the formation of smaller ice crystals [ 52 , 53 ]. During freezing, food structures might be under the influence of ice crystal formations within and outside the cells [ 49 ].…”
Section: Effect Of Freezing On Food Qualitymentioning
confidence: 99%
“…When water was stored at -11°C, an oscillating magnetic eld (OMF) intensity of 50 mT kept water supercooled without freezing, whereas an OMF intensity of more than 100 mT induced icing (Kang et al, 2021). However, it has also been reported that distilled water and a 0.9% NaCl solution treated with a weak OMF (0.8 mT) and a frequency range of 20-2000 Hz showed no signi cant supercooling (Otero et al, 2020).…”
Section: Introductionmentioning
confidence: 99%